Active versus restrictive approach to isolated hypotension in preterm neonates: A Systematic Review, Meta-analysis and GRADE based Clinical Practice Guideline. - Viraraghavan Vadakkencherry Ramaswamy; Gunjana Kumar; Abdul Kareem Pullattayil S; Abhishek S Aradhya; Pradeep Suryawanshi; Mohit Sahni; Supreet Khurana; Kiran More; National Neonatal Forum, India, Clinical Practice Guidelines Group on Neonatal Shock (PLoS ONE)
Objective Isolated hypotension (IH) without any clinical or biochemical features of poor perfusion is a common occurrence in very preterm infants (VPTI). There exists no recommendations guiding its management.The objective of this review was to compare the effect of active vs. restrictive approach to treat IH in VPTI. Methodology Medline, Embase and Web of Science were searched until 1st April 2024. RCTs and non-RCTs were included. Mortality, major brain injury (MBI) (intraventricular hemorrhage >  grade 2 or cystic periventricular leukomalacia), mortality or neurodevelopmental impairment (NDI) at 18-24 months' corrected age were the critical outcomes evaluated. Results 44 studies were included: 9 were synthesized in a meta-analysis and 35 studies in the narrative review. Clinical benefit or harm could not be ruled out for the outcomes from the meta-analyses of RCTs. Meta-analysis of 3 non-RCTs suggested that active treatment of IH in VPTI of <  24 hours of life possibly increased the odds of MBI (aOR: 95% CI 1.85 (1.45; 2.36), very low certainty). Meta-analysis of 2 non-RCTs that had included VPTI <  72 hours indicated a possibly decreased risk of MBI (aOR: 95% CI 0.44 (0.24; 0.82), very low certainty) and NEC ≥  stage 2 (aOR: 95% CI 0.61 (0.41; 0.92), very low certainty) with active treatment of IH. Active treatment of IH in the first 24 hours possibly increased the risk of mortality or long-term NDI (aOR: 95% CI 1.84 (1.10; 3.09), very low certainty) and the risk of hearing loss at 2 years (aOR: 95% CI 3.60 (1.30; 9.70), very low certainty). Clinical benefit or harm could not be ruled out for other outcomes. There was insufficient evidence with respect to preterm neonates of ≥  32 weeks. Conclusions IH may not be treated in VPTI in the first 24 hours. However, IH occurring between 24 hours - 72 hours of life may be treated. The evidence certainty was very low.